ANALISIS FRAMING LITERASI LINGKUNGAN DI KAWASAN BEBAS SAMPAH KOTA BANDUNG - Siswantini Siswantini; Arsiyanti Lestari (Jurnal Ilmu Komunikasi Acta Diurna, 2018)
The challenge of managing waste in the future is to develop zero waste city, however the condition will never be achieved without community participation. In colaboration with NGO which work in waste and garbage management issue, the local government had developed the model of zero waste area in district level. This article is aims to explore the framing of waste management literacy event in Kampung Cibunut. Applying the framing theory of McLachan and Reid, the analysis arrive to the result that continuing interaction among facilitator and cadres and community member has built the shift framing and counter framing. There is also flixed framing which display the resistence to frame change or modification such as the indicators of zero waste area, and flexible framing which display the opennes to frame change or modification such as the implementation of skill transfer in public areas. Entire framing was develop from contextualization of the message delivered in literacy event.